2004
DOI: 10.1007/bf02946735
|View full text |Cite
|
Sign up to set email alerts
|

A survey of aflatoxin B1 and total aflatoxin contamination in baby food, peanut and corn products sold at retail in Indonesia analysed by ELISA and HPLC

Abstract: Aflatoxin contamination has been well known as a world-wide health-threatening problem in tropical countries including Indonesia. This research was undertaken to determine the degree of aflatoxin contamination in different Indonesian foodstuffs. A preliminary survey was carried out to evaluate the level of total aflatoxin (AfT) and aflatoxin B1 (AfB1) contamination of baby foods, peanut products, and corn products, which were purchased from traditional markets and supermarkets in Indonesia during the year 2001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Based on previous studies (Bankole et al, 2010;Egal et al, 2005;Ok et al, 2007;Razzazi-Fazeli et al, 2004;Shundo et al, 2009;Williams et al, 2004), a wide range of foods could be contaminated by AFT, which are commonly associated with groundnuts, tree nuts, dried fruit, spices, rice, maize, soybeans, and wheat, and high incidences (between 12% and 85%) and high AFB 1 levels (from 10 to 1099 mg/kg) were found in most developing countries, particularly for peanut products. Compared with reports from other countries, the studies of Chen (1997) from JECFA found that soybean and its products, maize, wheat, sorghum, rice, and peanuts and its products were contaminated with AFB 1 in China, and peanuts had lower levels (0.6e488 mg/kg) than other countries.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on previous studies (Bankole et al, 2010;Egal et al, 2005;Ok et al, 2007;Razzazi-Fazeli et al, 2004;Shundo et al, 2009;Williams et al, 2004), a wide range of foods could be contaminated by AFT, which are commonly associated with groundnuts, tree nuts, dried fruit, spices, rice, maize, soybeans, and wheat, and high incidences (between 12% and 85%) and high AFB 1 levels (from 10 to 1099 mg/kg) were found in most developing countries, particularly for peanut products. Compared with reports from other countries, the studies of Chen (1997) from JECFA found that soybean and its products, maize, wheat, sorghum, rice, and peanuts and its products were contaminated with AFB 1 in China, and peanuts had lower levels (0.6e488 mg/kg) than other countries.…”
Section: Resultsmentioning
confidence: 97%
“…(Bankole, Adenusi, Lawal, & Adesanya, 2010;Ok et al, 2007;Razzazi-Fazeli, Noviandi, Porasuphatana, Agus, & Böhm, 2004;Shundo, Navas, Lamardo, Ruvieri, & Sabino, 2009;Soubra, Sarkis, Hilan, & Verger, 2009). However, the major contributor to AFT exposure is unclear, considering the different dietary habits in different regions.…”
mentioning
confidence: 97%
“…Ochratoxin A was detected in fourteen of the samples (limit of detection 0.035 µg·kg -1 ). In another survey Razzazi-Fazeli et al [30] examined twelve baby foods and found no aflatoxins in the products. Sewram et al [31] investigated corn-based infant food from markets in Brazil.…”
Section: Occurrence Of Mycotoxigenic Fungi and Mycotoxins In Infant Fmentioning
confidence: 99%
“…The maximum level of all finished wheat products intended for human consumption should be less than 1000 mg DON/kg (CAST, 2003;Chesemore, 1993 Occurrence data of mycotoxins in agricultural products from South East Asia, especially Indonesia, is limited. A survey to evaluate contamination of aflatoxins in Indonesian foods, particularly peanuts and peanutebased products, collected in the period of 2001e2002 was carried out by Razzazi-Fazeli, Noviandi, Porasuphatana, Agus, and Böhm (2004). The occurrence of some Fusarium toxins such as fumonisins, nivalenol, and zearalenone in maize and maize-based product samples was also reported by Yamashita, Yoshizawa, Aiura, Sanchez, Dizon, Arim et al (1995) and Nuryono, Noviandi, Böhm, Agus, Wedhastri, Maryudani et al (2004) and Nuryono, Noviandi, Böhm, and Razzazi-Fazeli (2005).…”
Section: Introductionmentioning
confidence: 99%